Applied operational research with SAS - Emrouznejad, Ali.; Ho, William (Boca Raton : Chapman and Hall/CRC, 2011)
"Using a wide range of operational research (OR) optimization examples, Applied Operational Research with SAS demonstrates how the OR procedures in SAS work. The book is one of the first to extensively cover the application of SAS procedures to OR problems, such as single criterion optimization, project management decisions, printed circuit board assembly, and multiple criteria decision making.The text begins with the algorithms and methods for linear programming, integer linear programming, and goal programming models. It then describes the principles of several OR procedures in SAS. Subsequent chapters explain how to use these procedures to solve various types of OR problems. Each of these chapters describes the concept of an OR problem, presents an example of the problem, and discusses the specific procedure and its macros for the optimal solution of the problem. The macros include data handling, model building, and report writing.While primarily designed for SAS users in OR and marketing analytics, the book can also be used by readers interested in mathematical modeling techniques. By formulating the OR problems as mathematical models, the authors show how SAS can solve a variety of optimization problems"--
"Preface This book was written primarily for SAS users in operational research, or simply OR. We use a wide range of OR optimization problems to demonstrate how the SAS/OR procedures work. The problems include single criterion optimization problems (e.g., transportation, assignment, transshipment, minimum-cost capacitated flow, maximum flow, shortest path, assembly line balancing, and traveling salesman), project management decision problems (e.g., critical path analysis, and program evaluation and review technique), printed circuit board (PCB) assembly problems (e.g., PCB assembly line assignment, PCB component allocation, and PCB component sequencing for pick-and-place machines), and multiple-criteria decision-making problems (e.g., analytic hierarchy process, multiple-criteria logistics distribution, ordered weighted averaging, data envelopment analysis, and Malmquist productivity index). The emphasis in this book is to use PROC OPTMODEL, which is the most recent development in SAS for optimization problems. The principles of several other procedures are also presented. We believe that this is the first book to extensively and successfully cover the application of SAS/OR procedures to OR problems. In addition, this book was written for undergraduate and postgraduate students in OR and those who are interested in mathematical modeling techniques. We formulated the OR problems mentioned earlier as various types of mathematical models, including linear programming, integer linear programming, and goal-programming models. We also show the transformation of the minima- type formulation into a minimization-type formulation"--
1. Operational research, algorithms, and methods -- 2. Transportation models -- 3. Network models -- 4. Project scheduling -- 5. Layout decision -- 6. Traveling salesman problem -- 7. Printed circuit board production planning -- 8. Multiple-criteria decision making -- 9. Decision making and efficiency measurement.
Includes bibliographical references and index.
Also available as an electronic resource.
Keywords: SAS (Computer file); Operations research -- Data processing